“Reflor-&-Ser”: a ginecologia natural como resistência à medicalização da vida e locus de percepção das agências do reino vegetal - Souza, Shiara Arruda de (2021)
This dissertation describes how latin-american movement called Natural Gynecology acts in Brazil through holistics therapists spread the principles of movement through various social medias. Natural Gynecology’s main guidelines are: promote women’s self-knowledge and women’s autonomy with regard to gynecological care. Problematizing “medicalization” of female body’s physiological events, embodied by discourses and practices of biomedicine, practitioners of Natural Gynecology rescue knowledges and so-called ancestral healing practices, mainly guided by medical plants. Nevertheless, while promoting important reflections on patriarchal and biomedical power, they still sustaining gender essensialist discourse. However, since the movement acts on social media, where varied social segments can follow it, transsexuals people stress the debate, leading Natural Gynecology to reconsider some essencialists perspectives. Furthermore, Natural Gynecology seeks to establish a relationship with the Plant Kingdom that values the agencies of plants, making it possible to reflect on the relationships of humans with other non-humans, thus demonstrating that reality is more-than-human.